Proposing a Typology of Ludification as a Translation Technique for PC, Console, Mobile and Online Games - SF. Luthfie Arguby Purnomo; SF. Lukfianka Sanjaya Purnama; Lilik Untari; Arynaa Azzahra; Nadya Octaviana Pramana Putri (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
Translation technique typology indicates a lack of specific technique to evoke playful nuance – ludification. We argue that ludification might also serve as a translation technique in video game translation context. This research attempts to prove the presence of ludification translation technique. To do so, we analyzed nine PC, console, mobile, and online games from various genres and developers under the umbrella of qualitative design. The theories of lability and merrines by Huizinga, ludification of digital media by de Lange et al, and skopos by Reiss and Vermeer were applied in the analysis. The findings reveal that ludification as a translation technique is existent. This type of translation technique is made possible due to the carte blanche of video game translators. The findings also indicate that ludification as a translation technique has a distinctive typology, making it different from the other translation techniques. First, it breaks translation rules and standards to generate contextual merriness. Second, it has explanative and expressive functions. Third, it has subtypes, namely emojization, referencing, and para-localization. This study implies that the scholars of translation studies might apply this typology not only on game translation context but also audiovisual context like subtitling especially fansub, where carte blanche and creativity are required to deal with the space restriction.